Cervical mucus changes can predict ovulation time in Mithun - RAMESH, VIKRAM; DEVI, LAISHRAM SUNITIBALA; JOSHI, VIVEK; HANAH, SAPUNII STEPHEN; KHATE, KOBU; KHAN, MERAJ HAIDER (The Indian Journal of Animal Sciences, 2024)
The study aimed to assess the possibility of cervical mucus changes to predict ovulation time in Mithun. Experimental Mithuns (n=6) were estrus synchronized and cervical mucus was collected in different estrus phases from three consecutive estrous cycles (n=18). Cervical mucus colour, consistency, arborization pattern and cytology were evaluated. Plasma estradiol-17β (E2) and progesterone (P4) levels were determined during different phases of estrous cycles. Ovulation time and subsequent growth of the corpus luteum were determined using transrectal ultrasonography. Results indicated thick and moderate cloudy mucus with a typical arborization pattern in midestrus. Sticky caseous or white-coloured thick consistency cervical mucus was observed during metestrus in 66.66% (n=14) estrous cycles along with ovulation or ovulation occurring within the range of -3 to + 4.5 - +7.5 h after the appearance of white mucus. Cervical mucus cytology revealed percentages of polymorphonuclear neutrophils were significantly higher in metestrus. E2 concentrations reached the peak on the day of estrus and P4 concentrations were lower than 0.5 ng/mL. It was concluded that cervical mucus shows a typical arborization pattern in midestrus and the appearance of characteristic sticky caseous cervical mucus during metestrus can be used as a tool to predict ovulation time.